Analisis Buku Teks Matematika Kelas VII Semester II Kurikulum 2013 Terbitan Erlangga Berdasarkan Pendekatan Saintifik - Angela Fitri, Jesica; Sumardi, Hari; Susanto, Edi (Jurnal Didactical Mathematics, 2021)
This research purposed to analyzed the suitability the presentation of the material in the mathematics textbook for seventh grade semester second of the 2013 Curriculum published by Erlangga chapter on geometry based on a scientific approach. The type of research was descriptive qualitative research. The facts studied in this research were the suitability of presenting material in textbooks based on a scientific approach using 2 data collection techniques, namely documentation and observation sheets. The results showed the suitability of presenting material in mathematics textbooks in the angles and parallel lines chapter of 81.56% included in the very suitable criteria. Percentage of the observing stage of 91,66%, questioning stage of 67,11% , experimenting stage of 97,22%, associating stage of 68,05%, and communicating stage of 83,77%. In the rectangular chapter, the level of conformity was 91.65%, which included in the very suitable criteria. Percentage of the observing stage of 100%, questioning stage of 85,05% , experimenting stage of 97,22%, associating stage of 86,88%, and communicating stage of 88,88%. In the triangle chapter had a high level of the suitability of 94.1% included in the very appropriate criteria. Percentage of the observing stage of 100%, questioning stage of 92,75%, experimenting stage of 100%, associating stage of 77,75%, and communicating stage of 100%.